The mediating effect of job satisfaction on leadership style and competency to organization commitment of employees in Group Top Glove Sdn. Bhd. - Lam, Ka Hou (2013)
This research is to identify the influence of leadership styles and competencies to the organization commitment of the employees in the glove manufacturing industry which are mediated by employees’ job satisfaction in the Klang’s Glove Manufacturing Industries. This study is based on samples collected from Operation Staff & Officers of various departments in a glove manufacturing industry, based on samples collected from employee in the Top Glove Corporation Bhd. in Klang, Selangor. There are two (2) independent variable which are leadership style (transformational & transactional) and leadership competency. Moreover, it is found that a positive relationship between transformational leadership style and organization commitment. The result of this study shows that a positive relationship between transactional leadership style and organization commitment. Results also confirmed the previous study that found a positive relationship between leadership competencies and organization commitment. When we are study mediating effect of job satisfaction on the relationship between leadership style and competencies with organization commitment. The results shown job satisfaction as being partially mediated the relationship between transformational leadership styles on organizational commitment. The study also reports that the job satisfaction as being partially mediated the relationship between transactional leadership styles on organizational commitment. The results had states job satisfaction as being partially mediated the relationship between leadership competencies on organizational commitment